إطار مقترح لبيان أثر الأبعاد الثقافية لهوفستيد على الفجوة الضريبية : دراسة ميدانية بالتطبيق على مصلحة الضرائب المصرية - سليمان، حنان الداودي عبده (جامعة قناة السويس - كلية التجارة بالاسماعيلية, 2016)
The research aims to study the cause of increasing the tax gap and demonstrate the impact of cultural dimensions of Hofstede on the increase. The research community TEMPhas been formed from all Egyptian financiers and foreigners residents in Egypt. Two samples of the Egyptian and foreign financiers was chosen. The researcher TEMPhas depended on survey for collecting data and the study found a relationship dat TEMPhas a statistical significant between the cultural dimensions of Hofstede and the tax gap dimensions. The study recommended dat the attention to the behavior of individuals to demonstrate the importance and the role of the tax on there public life.
يهدف البحث إلى دراسة أسباب زيادة الفجوة الضريبية وبيان أثر الأبعاد الثقافية لهوفستيد على هذه الزيادة، وقد تكون مجتمع البحث من جميع الممولين المصريين والأجانب المقيمين بمصر، وتم اختيار عينتين من الممولين المصريين والأجانب، واعتمدت الباحثة في جمع البيانات على الاستقصاء. وتوصلت الدراسة إلى وجود علاقة ذات دلالة إحصائية بين الأبعاد الثقافية لهوفستيد وبين أبعاد الفجوة الضريبية. وقد أوصت الدراسة بضرورة الاهتمام بالجانب السلوكي لدى الأفراد لبيان أهمية ودور الضريبة على حياتهم العامة.
Keywords: الضرائب; الفجوة الضريبية; مصلحة الضرائب المصرية